Aloe vera and lemon juice capability in decreasing formaldehyde content in tofu sumedang with cold storaging. (May 2019) - Daniela, C; Rusmarilin, H; Sinaga, H
Abstract: Formalin compounds are carcinogenic but are often used as preservatives for foods such tofu, which is harmful to health. This study aims to determine the concentration, soaking time of Aloe vera and lemon juice and the duration of cold storage to decrease formalin in tofu Sumedang. In this study, tofu was soaked in 5% formalin. Formalin tofu soaked with aloe and lemon juice in comparison (100%:0%, 80%:20%, 60%:40%, 40%:60%, 20%:80%, 0%:100%) and long immersion (30, 60, 90 (minutes)). Tofu with the best comparison and soaking is stored in cold storage (10 °C) for 0, 3, 6 and 9 (days). The results showed that 100% Aloe vera with 90 minutes immersion reduced formalin levels by 65, 82%, formalin residues by 28.777ppm, texture (5.592 (N/cm 2 ), pH (5.273), brightness (84.287) and color index (83.519). Search results for cold storage for as long as 3, 6, 9 (days) respectively, formalin (26.261 ppm, 25.510 ppm, 23, 440 ppm), texture (5.104, 4.325, 2.758), pH (5.043, 4.62, 3.92), mirror (79.916, 79.803, 79.410) and colour index (82.988, 83.514, 83.699). Aloe vera juice 100% containing saponin levels of 570µg/ml was more effective in removing formalin levels in Sumedang tofu because saponins as surfactants that bind formalin and air-soluble.